Exploring the heart and the mind - The Center for Humanities (Mount Kisko, N.Y. The Center, 1986)
Presents artists who were contemporary with the impressionists but sought to convey a more personal vision--an approach commonly called expressionism. Traces the history of expressionism and its influence on contemporary artists.
VHS
Keywords: Expressionism (Art).; Art, Modern -- 20th century; Art studies; Humanities